Study of Business Law Related to the Sale and Purchase of Inherited Land - Humala Sitinjak; Jenriswandi Damanik; Imman Yusuf Sitinjak (International Journal of Artificial Intelligence Research, 2022)
Property rights can be transferred to other parties because there is a legal event. The occurrence of a legal event is that with the death of the right holder, the property right passes from the right holder to his heirs, so that the heirs are obliged to register the transfer of rights due to land inheritance. Property rights can also be transferred due to legal actions, such as buying and selling, exchanging, grants to other parties. Â This research analyzes data qualitatively with a normative approach method which will examine the object based on legislation. Source of data used is secondary data. Data collection tools used with documentation studies. The location of the research implementation in Toba Regency. Regarding problems that have been bought and sold but not transferred by the next owner until the land has inherited status, when registering the land or changing the name of the land certificate, you need to ask for evidence of the history of the land, which can be letters of compensation, sale and purchase or other documents. others that are related as evidence and will later become an important part when the land will be passed on to descendants in the event of death